Audit Characteristics and the Likelihood of Occurring Financial Reports Suspicious of Fraud - Frehner Poffo, Rubia; Voltolini Gomes, Adhmir Renan; Bubeck, Stephan Klaus; Hein, Nelson (Review of Business Management, 2025)
Purpose – Analyze the relationship between audit characteristics and the likelihood of occurrence of financial reports suspected of fraud in companies. Theoretical framework – Agency Theory Design/methodology/approach – Descriptive, documentary and quantitative research, using the methods of Approximate Set Theory, k-means cluster analysis and logistic regression. The sample consists of 211 Brazilian companies listed on [B]3, considering the years between 2016 and 2021, from the Refinitiv database. Findings – The results indicate that Big Four audits reduce the chances of fraudulent-like financial reporting (FLFR) in Brazil, providing greater security to stakeholders. However, changing auditing practices and the financial independence of the audit firm do not significantly influence the detection of FLFR. On the other hand, qualified opinions increase the chances of FLFR by 3.625 times, and with a disclaimer of opinion, by 62.22 times, highlighting such opinions as the main indicators for identifying FLFR. Research Practical & Social implications – Considering the number of publicly traded companies that make up [B]3, and the number of shares that are traded daily in Brazil, there is a need to understand the relationship between the characteristics of the audit and the FLFR in the Brazilian organizational scenario. Originality/value – The research differs from others, as it shows that the types of opinions issued by auditors may indicate the possibility of FLFR occurring.